2003
DOI: 10.1042/bj20021166
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the human Sp1 gene promoter by the specificity protein (Sp) family members nuclear factor Y (NF-Y) and E2F

Abstract: We analysed in detail the minimal promoter of transcription factor Sp1, which extends 217 bp from the initiation of transcription. Within this sequence we identified putative binding sites for Sp1, nuclear factor Y (NF-Y), activator protein 2 ('AP-2'), CCAAT/enhancer-binding protein ('C/EBP') and E2F transcription factors. In one case, the boxes for Sp1 and NF-Y are overlapping. Gel-shift and supershift assays demonstrated specific binding of Sp1, Sp3 and NF-Y proteins. Transient transfections and luciferase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 55 publications
6
43
0
Order By: Relevance
“…There are several putative E2F-binding motifs in the promoters of viral genes such as BRLFI [66], BALF4, BRRF2, BVRF1 and BPLF1 (Kudoh and Tsurumi; unpublished results) besides BALF5 10 10 T. Tsurumi T. Tsurumi et al et al [62]. Also, E2F putative binding sites have been identified within the promoter of the cellular transcription factor Sp1 [67] and E2F exerts an additive effect on its overexpression. Within the EBV lytic gene promoters there are many Sp1 binding sites.…”
Section: Cell Cycle Arrest Induced By the Ebv Lytic Programme Is Not mentioning
confidence: 92%
“…There are several putative E2F-binding motifs in the promoters of viral genes such as BRLFI [66], BALF4, BRRF2, BVRF1 and BPLF1 (Kudoh and Tsurumi; unpublished results) besides BALF5 10 10 T. Tsurumi T. Tsurumi et al et al [62]. Also, E2F putative binding sites have been identified within the promoter of the cellular transcription factor Sp1 [67] and E2F exerts an additive effect on its overexpression. Within the EBV lytic gene promoters there are many Sp1 binding sites.…”
Section: Cell Cycle Arrest Induced By the Ebv Lytic Programme Is Not mentioning
confidence: 92%
“…Sp1 not only regulates the expression of multiple genes, but also the Sp1 gene itself (Nicolás, et al, 2003;Tapias, et al, 2008). Abnormal Sp1 protein levels have been observed in several cancers Safe, et al, 2014;Sankpal, et al, 2012;Wang, et al, 2003).…”
Section: Sp1 Is Involved In Cell Growth and Tumorigenesismentioning
confidence: 99%
“…Although a number of studies have reported gene regulation by Sp1, few have reported the transcriptional regulation of Sp1 itself. One recent study showed that the Sp1 promoter contains a number of putative binding sites for several transcription factors, including Sp1, Sp3, nuclear factor Y, activator protein 2, and CCAAT/enhancer-binding protein (13,14). Because the Sp1 promoter contains putative Sp1 binding sites, Sp1 overexpression may result from autotransactivation of its own promoter.…”
mentioning
confidence: 99%
“…2C). A previous study reported that a minimal Sp1 promoter (À217 bp upstream of the transcription initiation site) contains binding sites for various transcription factors, including Sp1, nuclear factor Y, activator protein 2, and CCAAT/enhancer-binding protein (13,14). We then tested the effect of KLF4 expression on this minimal Sp1 promoter luciferase reporter.…”
mentioning
confidence: 99%